A Review of Optimization of Energy Efficiency Though Phase Change Material in Building - Simran Jauhari (International Journal of Urban Design and Development, 2023)
Energy use in the construction sector is substantial. Thus, it is crucial that new materials be developed with the intention of improving building thermal efficiency. Thus, over the last few decades, the incorporation of Phase Change Materials has increased. (PCMs) into buildings has gained popularity. Such materials, which have the capacity to both absorb and release energy from/in the environment, can lessen temperature variations, enhancing human comfort while also consuming less energy during construction. This study looks at current experimental research on passive building systems that use mortars or PCMs that contain concrete. This review is primarily intended to provide information on the currently investigated materials as well as the manufacturing methodologies employed.
Keywords: Building substances; Concrete; Phase-Changing Material (PCM); inactive constructing systems; mortar; thermal power storage